2015
DOI: 10.1089/cell.2014.0110
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell–Derived Bioactive Materials Accelerate Development of PorcineIn Vitro–Fertilized Embryos

Abstract: Stem cells show the capability to proliferate in an undifferentiated state with long-term self-renewal, which gives the cells advantages for use as bioactive material (BM) for embryo culture in vitro. The objective of this experiment was to investigate the effect of two BMs-human adipose tissue-derived mesenchymal stem cell BM (hAT-MSC-BM) and human embryonic stem cell-derived BM (hESC-BM)-on porcine embryo development compared to commonly used bovine serum albumin (BSA) or serum treatment groups. In vitro-fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 47 publications
0
5
0
1
Order By: Relevance
“…Western blots were performed essentially as described previously (Lee, Moon, Kim, & Park, ). In brief, oocytes (40 per sample) were solubilized in 20 μl of 1 × sodium dodecyl sulfate (SDS) sample buffer (62.5 mM Tris‐HCl, pH 6.8, containing 2% (w/v) SDS, 10% (v/v) glycerol, 50 μM dithiothreitol, and 0.01% (w/v) bromophenol blue or phenol red) and heated for 5 min at 95°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blots were performed essentially as described previously (Lee, Moon, Kim, & Park, ). In brief, oocytes (40 per sample) were solubilized in 20 μl of 1 × sodium dodecyl sulfate (SDS) sample buffer (62.5 mM Tris‐HCl, pH 6.8, containing 2% (w/v) SDS, 10% (v/v) glycerol, 50 μM dithiothreitol, and 0.01% (w/v) bromophenol blue or phenol red) and heated for 5 min at 95°C.…”
Section: Methodsmentioning
confidence: 99%
“…Western blots were performed essentially as described previously (Lee, Moon, Kim, & Park, 2015). In brief, oocytes ( p values < .05 were considered significant.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Treatment with stem cell factor, a growth factor that reduces cellular apoptosis, increases BCL2L1 expression, while antiapoptotic genes are poorly expressed in degenerative embryos (Felici et al, 1999). A recent study reported that treatment of in vitro fertilized porcine oocytes with mesenchymal stem cell‐derived bioactive material (hAT‐MSC‐BM) and human embryonic stem cell‐derived bioactive material (hESC‐BM) increases expression of transcription factors including POU5F1 and SOX2 , as well as antiapoptotic genes including BCL2L1 and BIRC5 (S. E. Lee et al, 2015). Another study reported that TNFAIP2, BAX, POU5F1 , and BCL2L1 are highly expressed in zinc‐treated in vitro fertilized blastocysts (Y. Jeon et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the addition of γ‐linolenic acid into the medium of bovine in vitro‐produced embryos promoted the developmental competence of zygotes and increased the cleavage rate until Day 2 (Gaja et al, ). Treatment with stem cell‐derived bioactive materials also accelerated the development of porcine in vitro‐ fertilized embryos (Lee, Moon, Kim, & Park, ). We found that rates of blastocyst development and over‐expanded blastocyst development were higher when embryos were treated with LPA starting on Day 4 post‐activation (Figure , Table ).…”
Section: Discussionmentioning
confidence: 99%